2020
DOI: 10.4168/aair.2020.12.5.750
|View full text |Cite
|
Sign up to set email alerts
|

The KAAACI/KDA Evidence-Based Practice Guidelines for Chronic Spontaneous Urticaria in Korean Adults and Children: Part 2. Management of H1-Antihistamine-Refractory Chronic Urticaria

Abstract: Quite a few patients with chronic spontaneous urticaria (CSU) are refractory to H 1 -antihistamines, even though the dose of H 1 -antihistamines is increased up to 4-fold. CSU that is not controlled with H 1 -antihistamines results in increased disease burden. Several immunomodulators have been used to manage these patients. The guidelines reported herein are connected to Part 1 of the KAAACI/KDA Evidence-Based Practice Guidelines for Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 88 publications
0
18
0
3
Order By: Relevance
“…Bishnoi et al [29] published a randomized prospective observer-blinded comparative study and found that after 90 days of treatment with NB-UVB, there was a decrease in the UAS to a mean value of 1.4, which was statistically significant. Although only very low-quality evidence is available, the KAAACI/KDA Evidence-Based Practice Guideline [15] suggests that NB-UVB phototherapy be used as add-on therapy in patients unresponsive to H1-antihistamines. Despite the growing acceptance of NB-UVB as an effective treatment modality in CU, few studies have systematically reviewed the advantages of NB-UVB phototherapy added to guideline-recommended antihistamine drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bishnoi et al [29] published a randomized prospective observer-blinded comparative study and found that after 90 days of treatment with NB-UVB, there was a decrease in the UAS to a mean value of 1.4, which was statistically significant. Although only very low-quality evidence is available, the KAAACI/KDA Evidence-Based Practice Guideline [15] suggests that NB-UVB phototherapy be used as add-on therapy in patients unresponsive to H1-antihistamines. Despite the growing acceptance of NB-UVB as an effective treatment modality in CU, few studies have systematically reviewed the advantages of NB-UVB phototherapy added to guideline-recommended antihistamine drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Other plausible mechanisms include apoptosis of dermal mast cells, immunomodulatory action and the production of anti-inflammatory cytokine [14]. The Korean Academy of Asthma, Allergy and Clinical Immunology (KAAACI) and the Korean Dermatological Association (KDA) Evidence-Based Practice Guideline suggests that narrowband UVB (NB-UVB) phototherapy can be added to H1-antihistamine treatment for the treatment of chronic spontaneous urticaria (CSU) and symptomatic dermographism [15]. However, to date, there has been no systematic review of NB-UVB phototherapy for treating CU.…”
Section: Introductionmentioning
confidence: 99%
“…Management guidelines for CU in past included omalizumab, cyclosporine, dapsone, hydroxychloroquine, methotrexate, montelukast, colchine, and phototherapy as alternative treatment for antihistamine-refractory CU [1,2]. However, most of recent guidelines recommend omalizumab for the first of choice among various immunomodulating agents based on lots of study results [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 10 ] Therefore, it is difficult to carry out targeted treatment of the cause, and only symptomatic treatment is currently available. [ 11 , 12 ] However, sometimes symptomatic treatment such as antihistamines cannot completely control the symptoms of CSU, [ 13 , 14 ] it will lead to a serious influence on the quality of life of patients, [ 15 ] and also greatly increase the pressure on public health. [ 16 , 17 ] Therefore, more effective and optimized treatments are required.…”
Section: Introductionmentioning
confidence: 99%